Aquaporin 4 blockade improves survival of murine heart allografts subjected to prolonged cold ischemia. Issue 5 (17th January 2018) - Ayasoufi, Katayoun; Kohei, Naoki; Nicosia, Michael; Fan, Ran; Farr, George W.; McGuirk, Paul R.; Pelletier, Marc F.; Fairchild, Robert L.; Valujskikh, Anna
Abstract : Prolonged cold ischemia storage (CIS) is a leading risk factor for poor transplant outcome. Existing strategies strive to minimize ischemia–reperfusion injury in transplanted organs, yet there is a need for novel approaches to improve outcomes of marginal allografts and expand the pool of donor organs suitable for transplantation. Aquaporins (AQPs) are a family of water channels that facilitate homeostasis, tissue injury, and inflammation. We tested whether inhibition of AQP4 improves the survival of fully MHC‐mismatched murine cardiac allografts subjected to 8 hours of CIS. Administration of a small molecule AQP4 inhibitor during donor heart collection and storage and for a short‐time posttransplantation improves the viability of donor graft cells, diminishes donor‐reactive T cell responses, and extends allograft survival in the absence of other immunosuppression. Furthermore, AQP4 inhibition is synergistic with cytotoxic T lymphocyte–associated antigen 4–Ig in prolonging survival of 8‐hour CIS heart allografts. AQP4 blockade markedly reduced T cell proliferation and cytokine production in vitro, suggesting that the improved graft survival is at least in part mediated through direct effects on donor‐reactive T cells. These results identify AQPs as a promising target for diminishing donor‐specific alloreactivity and improving the survival of high‐risk organ transplants. Abstract : Using a robust mouse model of heart allograft rejection, this study provides the first evidence that aquaporin water channels regulate adaptive alloimmunity and can be targeted to improve transplant outcome.